"IMPROVING THE USE OF MODERN FINANCIAL TECHNOLOGIES IN THE BANKING SYSTEM" - Parpiyeva Ra’no Abdurasulovna (Web of Journals Publishing, 2025)
In the digital economy, the introduction of modern financial technologies in banking activities significantly increases the competitiveness of banks. In this regard, digital banks have an accelerating effect on economic activity, allowing them to carry out financial transactions anytime and anywhere.
Keywords: Financial technologies, transformation, banking services, digital banking, innovation, modern technologies, applications.